Posture Monitoring via Mobile Devices - SmartVest Case Study - Machado Neto, Olibário J.; Pereira, Amanda Polin; Elui, Valéria Meirelles C.; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2016)
The SmartVest (Smart from “smartphone” and Vest from “vestiment”) is a solution created to help users with motor disabilities to correct their postures while performing daily activities. By means of a thoracic holder made of neoprene, a smartphone is placed to the user’s chest. The smartphone is equipped with an application that uses the coordinates of the accelerometer to identify the variation of the position of the user’s body in relation to a previously-calibrated position, which represents the adequate posture of the user. The application, called Postural, was built upon a software architecture that aims to facilitate the development of accessible applications for mobile devices used by persons with motor disabilities. The solution was tested in two phases. The first considered four users, while the second considered three users, all healthy. In the first phase, an occupational therapist who works with rehabilitation of people with hemiplegy and hemiparesis due to stroke was involved. The results indicated that the solution is promising for identifying and correcting the user’s posture, and can help both healthy users and people with hemiplegy and hemiparesis